The Relationship Between the Frequency of Antenatal Care Visits and Early Detection of Preeclampsia Risk in Pregnant Women in the Third Trimester - Rohmi, Rohmi; Rahmat, Rezqiqah Aulia (International Journal of Health Sciences, 2025)
Background:Preeclampsia is a pregnancy complication that contributes to high maternal morbidity and mortality rates. Regular antenatal care (ANC) visits can help detect risk factors for preeclampsia early, allowing for faster treatment. Objective:To determine the relationship between the frequency of ANC visits and early detection of the risk of preeclampsia in pregnant women in the third trimester. Method:This study used a cross-sectional analytical design on 85 pregnant women in their third trimester at Community Health Center X during March–May 2025. Data were collected through questionnaires and medical records. Data analysis used the Chi-Square test with a significance level of 0.05. Results:The majority of respondents had a standard ANC visit frequency of ≥4 times (68.2%), and 21.2% of them were diagnosed as being at risk for preeclampsia. Analysis showed a significant association between ANC visit frequency and early detection of preeclampsia risk (p=0.021). Conclusion:A standardized frequency of ANC visits is associated with increased early detection of preeclampsia risk. Education on the importance of regular ANC needs to be improved.